Development of Norms for Span of Attention and Span of Reading among 8 -12 Year Old Children - Tity Joseph (Sr),; Immanuel Thomas, (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The purpose of the present study is to development of norms for span of attention and span of reading among 8 -12 year old children. The sample of the present study consisted of 200 students. Who were divided in to 5 groups based on age. Each group consisted of equal number of students (20 students in the boys and 20 students in the girls. There were 100 boys and 100 girls in the sample. The sample consisted of students from class 3rd-7th following CBSE scheme of Trivandrum district in Kerala. The tools used for the study, personal computer, span of attention task, span of reading task. The data were analyzed using, analysis of variance, correlation and factor analysis. The result of the study showed that different age groups differ significantly in span of attention and span of reading, there is no significant gender difference in span of attention and span of reading, span of attention and span of reading are independent dimensions.
Keywords: Span of attention; Span of reading